Developing final as-built BIM model management system for owners during project closeout: A case study. (April 2018) - Lin, Yu-Cheng; Lin, Cheng-Ping; Hu, Hsin-Tzu; Su, Yu-Chih
Abstract: To apply final as-built BIM models to facility management (FM) during the operation phase, it is important for owners to obtain an accurate, final as-built model from the general contractors (GCs) following project closeout. Confirming the accuracy of the final as-built BIM model is one of the most important works executed by owners to meet the accuracy requirement of final as-built models for FM. However, many practical problems arise relating to the management of final as-built models such as final as-built model mismatch, the lack of available final as-built models, and the entry of incorrect non-geometric information into the final as-built models. To solve these practical problems, this study develops a Final As-built BIM Model Management (FABMM) system for owners to handle final as-built BIM model inspection, modification, and confirmation (BMIMC) work beyond project closeout. The proposed approach and system can be used to manage the status and results of BMIMC management work for the final as-built BIM model to be performed. The proposed approach and system were applied in a case study in a selected building in Taiwan to verify and demonstrate its practical effectiveness. This study identifies the benefits, limitations, and conclusions of the FABMM system, and presents suggestions for its further application.